Fukuyama, Francis. Political Order and Political Decay. From the Industrial Revolution to the Globalization of Democracy. Nueva York: Farrar, Strauss y Giroux, 2014, 658 pp. - Daniel Luna, Erich (2014)
No presenta resumen